2018
DOI: 10.1016/j.athoracsur.2017.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Should Diabetes Be a Contraindication to Bilateral Internal Mammary Artery Grafting?

Abstract: Among diabetics undergoing CABG, use of BIMA grafting does not result in increased in-hospital morbidity or mortality and confers a long-term survival advantage when compared with SIMA grafting. Thus, diabetic patients should be considered for BIMA grafting more frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
1
12
1
2
Order By: Relevance
“…In contrast to our findings of higher mortality in the diabetic BIMA population (versus LIMA), Gansera and colleagues [7] identified significantly lower rates of operative mortality (3.1% vs 4.7%) in diabetic BIMA (versus single internal mammary artery) patients [17]. Furthermore, multiple previous studies have demonstrated similar rates of operative mortality and significantly reduced hazard for longterm mortality among diabetic patients who received BIMA versus single internal mammary artery grafts [18][19][20]. However, all of these previous studies were retrospective and limited to a single institution or to a regional collaborative.…”
Section: Commentcontrasting
confidence: 76%
“…In contrast to our findings of higher mortality in the diabetic BIMA population (versus LIMA), Gansera and colleagues [7] identified significantly lower rates of operative mortality (3.1% vs 4.7%) in diabetic BIMA (versus single internal mammary artery) patients [17]. Furthermore, multiple previous studies have demonstrated similar rates of operative mortality and significantly reduced hazard for longterm mortality among diabetic patients who received BIMA versus single internal mammary artery grafts [18][19][20]. However, all of these previous studies were retrospective and limited to a single institution or to a regional collaborative.…”
Section: Commentcontrasting
confidence: 76%
“…But they speculate that there is evidence that late outcome of surgical revascularization is improved when at least two arterial grafts are used and conclude that every patient should receive arterial grafts. In a PS-matched analysis among diabetic patients with a median duration of followup of 9.3 years, 23 patients who received a BIMA also had significantly improved long-term survival when compared with SIMA patients. Our data do not support these earlier results in diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown the superiority of arterial grafts over venous grafts in terms of long-term survival, need of repeated revascularization, and graft failure [28,29,31,32] without impact on in-hospital mortality [33]. But in our practice, and for a long time, we considered diabetes as an absolute contraindication to BITA harvesting because of the "inevitable and frightening" mediastinitis.…”
Section: Discussionmentioning
confidence: 98%
“…However, BITA was indicated in the univariate analysis but was not significant in multivariate analysis as an independent predictor of mediastinitis. Even if several recent publications [28,29] claimed that BITA use has not been associated with an increased risk of mediastinitis compared to SITA, the debate remains; Taggart et al [30] had published the 5-year results of ART investigation and found that BITA was significantly associated with higher rate of both sternal wound complications and sternal reconstructions without benefit of survival or freedom from adverse events at 5 years. However, it seems that the risk can be lowered if graft harvesting was made by skeletonized fashion with meticulous attention to preserve sternal blood flow [31,32].…”
Section: Discussionmentioning
confidence: 99%